Selection associated with the alcohol dehydrogenase locus in Drosophila melanogaster: Differential survival of adults maintained on low concentrations of ethanol. - Daly, K.; Clarke, B. (Heredity, 1981)
David and his collaborators have reported that adult Drosophila melanogaster survive longer on 2 per cent ethanol than on distilled water, but that the increased survival on ethanol does not occur in mutant flies lacking alcohol dehydrogenase activity. This has led us to enquire if the polymorphic alleles at the alcohol dehydrogenase locus (AdhF and AdhS), which code for enzymes with different activities, affect survival on low concentrations of ethanol. Flies were kept in sealed glass chambers containing either 2 per cent ethanol or distilled water. In four experiments, comprising a total of 126 replicates, the proportion of surviving FF flies, relative to SS, was greater on ethanol than on water. In two experiments the excess was highly significant. It appears that FF flies are better able than SS to use ethanol as food. Our results support the view that selection acts directly on the Adh polymorphism.